Improving the Cost Factor of DLBCA Lightweight Block Cipher Algorithm - Sufyan Salim Mahmood AlDabbagh; Alyaa Ghanim Sulaiman; Imad Fakhri Taha Al Shaikhli; Khalid Abdulkareem Al-Enezi; Abdulrahman Yousef Alenezi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The needing to secure information in restricted environments is very important so that lightweight block cipher algorithm is suitable for these environments. This paper improved DLBCA algorithm by decreasing the cost factor through using the less number of S-boxes. Also, differential and boomerang attacks have been applied in this paper. Finally, all the results have been presented